1996
DOI: 10.4319/lo.1996.41.7.1394
|View full text |Cite
|
Sign up to set email alerts
|

Jellyfish Lake, Palau: Regeneration of C, N, Si, and P in anoxic marine lake sediments

Abstract: Sediment cores from Jellyfish Lake were processed under an inert atmos phcre and the pore waters extracted and analyzed for the following parameters: pH, titration alkalinity (TA), Cl-, H4Si04, POd3-, NH4+, Ca2+, Mg2+, SOd2-, and H2S. Additionally, in one set of pore-water samples (core lo), the 613C of the X0, was also determined. The TA, H4Si04, POd3-, NH;+, and H,S increased with depth in the pore waters above anoxic bottom-water values. H,S values increased to 3.8 PM. In one case, both H,SiO, and POd3-conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…The lower DF concentration was chiefly found in the subsurface layer during spring and summer corresponding with a higher DRP concentration. Such lower concentrations of DF in the pore water of marine sediments have been reported for other coastal regions (Ruttenberg and Berner, 1993) and for a saline water lake (Lyons et al, 1996). In these observations, contemporaneous high concentrations of DRP in the pore water were also found.…”
Section: Seasonal and Vertical Variations Of Interstitial Phosphate Asupporting
confidence: 65%
See 3 more Smart Citations
“…The lower DF concentration was chiefly found in the subsurface layer during spring and summer corresponding with a higher DRP concentration. Such lower concentrations of DF in the pore water of marine sediments have been reported for other coastal regions (Ruttenberg and Berner, 1993) and for a saline water lake (Lyons et al, 1996). In these observations, contemporaneous high concentrations of DRP in the pore water were also found.…”
Section: Seasonal and Vertical Variations Of Interstitial Phosphate Asupporting
confidence: 65%
“…The phosphorus to fluorine (P/F) atomic ratio of CFA has been reported to be in the range 2/1-5/1 (Parker, 1975;Burnett, 1977;Jahnke, 1984;Gulbrandsen et al, 1984;Baker and Burnett, 1988;Froelich et al, 1988). Although it has been suggested that CFA forms in reductive non-phosphogenic sediment (Sundby et al, 1992;Lyons et al, 1996;Louchouarn et al, 1997), the existence of CFA has not been confirmed in such sediment. Phosphorus contents of marine sediment are generally less than 1000 ppm making the contents difficult to analyze by either nondestructive analysis (such as X-ray diffraction) or isolation of the mineral for chemical analysis (e.g., Ruttenberg and Berner, 1993).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In both NLK and OTM, low CR and high NCP near the chemocline suggest a substantial flux of organic matter from the upper portion of the lake into deeper layers. However, Lyons et al (1996) estimated that in OTM only 4% of autochthonous organic matter is deposited on the lake bottom, with vertical stratification slowing the decent of phytoplankton-derived organic matter.…”
Section: Patterns In Gpp Cr and Ncp Within And Across Marine Lakesmentioning
confidence: 99%